How to be happy at work the power of purpose, hope and friendships - McKee, Annie 1955- (Boston, Massachusetts Harvard Business Review Press, 2018)
"I'm working harder than I ever have, and I don't know if it's worth it anymore." If you're a manager or leader in today's high-speed, high-stress economy, these words have probably run through your mind, maybe more than once. Many people in management positions are feeling fed up, burned out, and unhappy at work: the constant pressure and stress, the unending changes, the politics . . . People are feeling they can't give much more, and their performance is suffering. But it's work, after all, right? Should we even expect to be fulfilled and happy at work? Annie McKee answers with a definitive yes. She makes the most compelling case yet that happiness--and the full engagement that comes with it--is more important than ever in today's workplace. Based on extensive research and decades of experience with leaders, this book sheds new light on the powerful relationship of happiness to individual, team, and organizational success. McKee's research reveals that there are three essential elements that people must have in order to be happy at work: A sense of purpose and the chance to contribute to something bigger than themselves; A vision that is powerful and personal, creating a real sense of hope; and Resonant, friendly relationships The book is organized around these essential elements and shows how leaders can create and sustain them in the face of ongoing stress and pressure, as well as how to create a healthy, positive climate for their teams and other groups within their companies. How to Be Happy at Work will transform and enrich our understanding of what it means to be happy at work, and it will provide clear, practical advice and instruction for how to achieve this.--Provided by publisher.
donated by The Asia Foundation (Books for Asia)
Keywords: Employee motivation; Friendship; Happiness; Hope; Personnel management; Quality of work life